Inclusivity In The Circular Economy: A Systematic Review Of Social Innovation In Developing Regions - Nurrohman, Rosyid; Bharata, Wira; Hikmah, Mukhibatul; Nurqamarani, Adisthy Shabrina; Utami, Rezki Aguswidya; Prasetyo, Agus (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
Purpose – This study examines how circular economy (CE) practices are developed through social innovation and community engagement in developing countries. It highlights CE not only as an environmental strategy but also as a pathway toward inclusive and sustainable development. Addressing the fragmented nature of CE literature, which often prioritizes technical efficiency while overlooking social participation, institutional support, and gender responsiveness, the study seeks to clarify how CE can be strengthened through grassroots entrepreneurship, community-led innovation, and multi-actor collaboration. Novelty – The originality of this research lies in integrating CE and social innovation literature with a specific focus on MSMEs in developing regions. By combining bibliometric and systematic review methods, the study moves beyond descriptive accounts and identifies theoretical mechanisms, key actors, and structural gaps that remain underexplored in mainstream CE scholarship. Method – A mixed-method approach was employed, integrating a Systematic Literature Review (SLR) with bibliometric analysis. A total of 189 Scopus-indexed articles published between 2010 and 2025 were selected using the PRISMA protocol. The Bibliometrix R-package was applied to examine keyword co-occurrence, thematic clusters, citation inequality, and author collaboration patterns, with particular attention to Global North–South imbalances. Findings – Results demonstrate a gradual shift in CE discourse in developing regions from technical-environmental models toward socially embedded approaches. Social innovation through women-led enterprises, cooperative networks, and community-based entrepreneurship emerges as a critical driver of inclusivity. The review also identifies three conceptual gaps: (1) limited theorization of inclusivity mechanisms in CE, (2) a lack of longitudinal and comparative studies, and (3) weak South–South collaboration and knowledge exchange. Limitations and Implications – This study is limited to English-language, Scopus-indexed publications, which may exclude grey or local-language literature, and it acknowledges methodological biases related to citation inequality and the dominance of Global North perspectives. Nonetheless, the findings provide actionable implications: policymakers should integrate gender-responsive policies into CE programs, strengthen local institutional support for MSMEs, and foster South–South learning platforms. Practitioners are encouraged to co-create inclusive CE models through multi-actor partnerships that enhance resilience, legitimacy, and long-term sustainability.